Endoscopic Atlas of Pediatric Otolaryngology - Cheng, Jeffrey; Bent, John P. (Springer International Publishing : Imprint: Springer, 2016)
This volume is an invaluable reference for the practicing pediatric otolaryngologist, including pediatric otolaryngology fellows and residents. Organized into primary chapters covering the topics of otology, rhinology, and laryngology/bronchoesophagology, each image is accompanied by a short description and brief overview/review of the pathology. While not meant to be all-encompassing of pediatric otolaryngology pathology encountered in practice, Atlas of Endoscopic Pediatric Otolaryngology is an essential tool for office and training programs to help educate the patient and family. .